PENGARUH JARAK TANAM DAN DOSIS PUPUK SP36 TERHADAP PERTUMBUHAN DAN HASIL TANAMAN KACANG HIJAU ( Phaseolus radiatus L) - Umi Kulsum; TEGUH SUPRIYADI; ENDANG SUPRAPTI (Fakultas Pertanian, Universitas Tunas Pembangunan Surakarta, 2016)
The objective of the researched was to distance plant and SP36 dosage fertilizer of growth and production Green Peanut plant was conducted at village Bagusan, Selopampang, Temanggung at 1st Juni until 1st September 2008. The land of Alfisol type (PPT Latosol) at the height 650 metre from see level. The research used factorial methode with elementary patten Completely Randomized Design (CRD), consisted of two treatment and the first factor was distance plant (J) : J1 = 20 x 20 cm, J2 = 20 x 30 cm, and J3 = 20 x 40 cm. The second factor was SP36 dosage fertilizer (P) : P0 = not SP36 fertilizer, P1 = 100 kg/ha, P2 = 125 kgh/ha and P3 = 125 kgh/ha, every treatment was 3 replicated. The result of research : (1). The distance plant treatment (J) not significant to the height of plant, the sum of trivoliat leaf, the sum legum planting, the weight legum planting, the weight dry seed blaze, the weight seed 100, the fresh weight of plant, the dry weight of plant parameters. But significant to weight ripe legum planting parameter and veri significant to the weight dry seed planting. (2). The SP36 dosage fertilizer we not significant to the height of plant, the sum of trivoliat leaf, the weight legum blaze, the weight dry seed blaze, the weight seed 100, the fresh weight of plant, the dry weight of plant parameters. But significant to the sum legum planting, the weignt ripe legum planting and the weight dry seed planting parameters. (3). The interaction of distance plant with SP36 dosage fertilizer were not significant to the height of plant, the sum of trivoliat leaf, the sum legum planting, the weight legum blaze, the weight dry seed blaze, the weight seed 100, the fresh weight of plant, the dry weight of plant parameters. But significant to the weight legum masak planting and very significant the weight dry seed planting, parameters. (4).Highest yield of the weight dry seed blaze was reach by J1P2 (interaction betwen distance plant 20 x 20 cm with SP36 dosage fertilizer 125 kg per Ha) that was 358,3 g equivalent with 0,75 ton per hektar, the lowest yield was J2P0 (interaction betwen distance plant 20 x 30 cm without SP36 fertilizer) that was 229,7 kg equivalent with 0,48 ton per hektar.